Performance of Hospital Information System in Malaysian Public Hospital: a Review - Desi Hertin, Revita; Ismael Al-Sanjary, Omar (International Journal of Engineering and Technology, 2018)
This paper presents an extensive literature review of Hospital Information System (HIS) in public hospital in Malaysia. This paper aims to deliver information (guideline) about the importance and benefits of HIS so that can help government to enhance the standard of healthcare quality. Accordingly, the Malaysian Government Ministry of Health (MoH) has presented three groups of HIS such as Basic Hospital Information System (BHIS), Intermediate Hospital Information System (IHIS), and Total Hospital Information System (THIS) amongst Malaysian government owned (public) hospitals. In Malaysia, there are 138 public hospitals but at this time only 21 hospitals implementing HIS. In this paper, researcher explains the three groups of HIS (THIS, BHIS, IHIS), the benefits, the challenges, the frameworks, also the current issues of HIS. Â